The Influence of Field Teaching Practice on Pre-service Teachers’ Professional Identity: A Mixed Methods Study - Zhao, Hongyu; Zhang, Xiaohui (Frontiers in Psychology, 2017)
The current study used mixed-methods to examine the changes in pre-service teachers’ professional identity in the stage of field teaching practice and the effects of field teaching practice on pre-service teachers’ professional identity and professional development in China. Ninety-eight pre-service teachers were investigated, and twelve teachers were interviewed. The results were as follows: (1) the results of quantitative data showed that pre-service teachers’ professional identity increased after the field teaching practice—specifically, intrinsic value identity increased, and extrinsic value identity remained steady; (2) the results of qualitative data were consistent with the results of quantitative data with regard to changes in professional identity. Specifically, intrinsic value identity (e.g., work content, work pattern) increased, and extrinsic value identity (e.g., work environment, income and social status) did not change after experiencing teaching practice; (3) the results of qualitative data also showed that mentor support at field school promoted the development of pre-service teachers’ professional identity. Moreover, the development of pre-service teachers’ professional identity during field teaching practice further promoted their professional commitment; that is, it promoted their emotional evaluation and belief in the teaching profession. The study discussed these results and proposed solutions and suggestions for future studies.